Penerapan Chatbot Pada Kerusakan Sepeda Motor Injeksi Dengan Basis Dialogflow dengan Telegram - Nugroho, Dwi Adi Mulyo; Wibowo, Jati Sasongko (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Damage to injection motorbikes can include various problems, from the fuel system, sensors, to electronic components, which can result in decreased engine performance and disruption to vehicle operation. The aim of this research is to find out and implement a Chatbot-based solution to overcome damage to injection motorbikes, based on Dialogflow and integrated with the Telegram instant messaging application. The main problem is the limited availability of data and the time needed to repair damage to injection motorbikes. The research methodology includes requirements analysis, system design, chat implementation on the Dialogflow platform, integration with Telegram, and evaluation of chat responsiveness through user testing. The black box test got a score of 100%, while the System Usability Scale (SUS) got a score of 85. The research results show that this chat implementation was successful in providing appropriate and responsive solutions to user questions. The conclusion of this research emphasizes that the use of Chatbots for injection motorbike damage using Dialogflow and Telegram can be an effective and efficient solution for providing technical assistance to users, thereby increasing the availability of information and reducing problem resolution time.